Product design activity as a process to develop a therapeutic toys for self-managed depression among adolescents - Muhammad Jameel Bin Mohamed Kamil; Gwendolyn Ho Wan Ying; Mohd Najib Bin Abdullah Sani (Journal of Graphic Engineering and Design, 2022)
Adolescent mental health issues are on the rise, with rates rising from one in ten in 2011 to one in five in 2016. This issue was predicted to be one of the top causes of global disability by 2020. Hence, with the aim to develop a therapeutic toy for self-managed depression, this paper intends to elucidate the product design process based on the criteria of therapies practiced by patients to manage mild and moderate depression. Semi-structured interviews were conducted with a clinical psychologist, three licensed counsellors, and six young depressive disorder patients as a methodology for gathering empirical data, which was then followed by the design process. The result of the interview indicates a multitude of design needs in self-managed depression. Therefore, a few design criteria have been proposed and a set of the non-working models of the therapeutic toys was successfully developed as a proposal for potential future development and production. It is hoped that the outcome of the study exhibits the synchronization of the design thinking process inside the ergonomics ergo system framework in order to generate the design for the patient.